Magnetic states and intervalence charge transfer of Ti and Fe defects in α-Al2O3: The origin of the blue in sapphire. (15th January 2018) - Na-Phattalung, Sutassana; Limpijumnong, Sukit; T-Thienprasert, Jiraroj; Yu, Jaejun
Abstract: We investigate the total energies and electronic structures of Ti-Fe pair defects in α -Al2 O3 by carrying out density-functional-theory calculations for various configurations of spin, charge, and orientation of Ti-Fe pair. From the total energy results, we show that the high-spin state of Ti IV -Fe II with an anti-ferromagnetic alignment between Ti and Fe is the ground state for both edge- and face-sharing orientations. Among several meta-stable states, the high-spin state of Ti III -Fe III with an anti-ferromagnetic alignment is connected to the Ti IV -Fe II ground state. An optical transition from the highest occupied Fe defect level to the lowest unoccupied Ti leads to an excited state of the high-spin Ti III -Fe III configuration together with a donation of electron from Fe II to Ti IV . It explains that the intervalence charge transfer from Ti IV -Fe II to Ti III -Fe III is responsible for the color of blue in sapphire. In addition, the total energies of Ti IV -Fe II ground state are found to be quite close within 0.02 eV for both edge- and face-sharing orientations, but the optical excitation energies for edge- and face-sharing orientations are 1.99 and 1.36 eV, respectively. Graphical abstract: Image